INDELseek: detection of complex insertions and deletions from next-generation sequencing data. (December 2017) - Au, Chun; Leung, Anskar; Kwong, Ava; Chan, Tsun; Ma, Edmond
Abstract Background Complex insertions and deletions (indels) from next-generation sequencing (NGS) data were prone to escape detection by currently available variant callers as shown by large-scale human genomics studies. Somatic and germline complex indels in key disease driver genes could be missed in NGS-based genomics studies. Results INDELseek is an open-source complex indel caller designed for NGS data of random fragments and PCR amplicons. The key differentiating factor of INDELseek is that each NGS read alignment was examined as a whole instead of "pileup" of each reference position across multiple alignments. In benchmarking against the reference material NA12878 genome (n  = 160 derived from high-confidence variant calls), GATK, SAMtools and INDELseek showed complex indel detection sensitivities of 0%, 0% and 100%, respectively. INDELseek also detected all known germline (BRCA1 andBRCA2 ) and somatic (CALR andJAK2 ) complex indels in human clinical samples (n  = 8). Further experiments validated all 10 detectedKIT complex indels in a discovery cohort of clinical samples.In silico semi-simulation showed sensitivities of 93.7–96.2% based on 8671 unique complex indels in >5000 genes from dbSNP and COSMIC. We also demonstrated the importance of complex indel detection in accurately annotatingBRCA1, BRCA2 andTP53 mutations with gained or rescued protein-truncating effects. Conclusions INDELseek is an accurate and versatile tool for complex indel detection in NGS data. It complements other variant callers in NGS-based genomics studies targeting a wide spectrum of genetic variations.